Building Customer Loyalty Through Customer Satisfaction Influenced by Social Media Marketing, Service Quality and Experiential Marketing - Carlianti, Ice; Syahyunan, Syahyunan; Fauzan Azhmy, Muhammad (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
This research aimed to investigate the impact of social media marketing, service quality, and experience-based marketing on consumer satisfaction and loyalty in the hospitality industry, specifically at Villa Kembali in Seminyak, Bali. The study involved 161 guests selected as respondents using the accidental sampling method and the Slovin formula. Data was collected through questionnaires and analyzed using the PLS-SEM approach. The results revealed that customer loyalty can be fostered through customer satisfaction and effective marketing strategies via social media or creating memorable guest experiences. On the other hand, customer satisfaction can be influenced by providing high-quality service, unique experiences, and utilizing social media for marketing purposes. The study also highlighted the importance of service quality in building and retaining customer loyalty. These findings can be valuable for the management of Villa Kembali in formulating strategies to enhance customer satisfaction and loyalty through social media promotions and top-notch services, as well as creating unforgettable experiences for their guests.